Rola i charakter publicystyki w paśmie regionalnym TVP na przykładzie analizy wybranych przekazów publicystycznych TVP Łódź - Grzegorzewski, Krzysztof (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The text describes selected publicistic programmes produced in 2013 by the regional branch of Polish National Television in Łódź. The author makes use of such analytical tools as modern rhetoric & stylistics, the study of non-verbal communication (including colours and their meaning), and mechanisms for persuasion and manipulation in the media. Based on the analysis carried out, the author assesses the quality of programmes and their role in the TV schedule, taking into account the context of their public mission.